2009
DOI: 10.1080/17480270903151233
|View full text |Cite
|
Sign up to set email alerts
|

Micromorphological studies of modified wood using a surface preparation technique based on ultraviolet laser ablation

Abstract: The objective of this paper is to demonstrate an ultraviolet (UV) laser ablation technique as a tool for sample preparation in microscopy studies of modified wood. Improved techniques for studying the microstructure of modified wood are crucial for a deeper understanding of many of their physical, mechanical and durability properties. The surface preparation technique is described in this paper. An illustration of micrographs of the micromorphology and polymer distribution in some examples of modified wood is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…At the higher level of furfurylation (WPG 45%), even more tracheids are filled with furan polymers (Figure 1g) and the cell walls seem to be slightly thicker compared to those of pine furf28 . This is consistent with the finding of Wålinder et al (2009) concerning the higher filling ratio of lumens at higher WPG levels. Additionally, as illustrated in Figure 1h,i, the furfurylated tracheids are completely or partly filled.…”
Section: D Microscopic Structuresupporting
confidence: 82%
See 2 more Smart Citations
“…At the higher level of furfurylation (WPG 45%), even more tracheids are filled with furan polymers (Figure 1g) and the cell walls seem to be slightly thicker compared to those of pine furf28 . This is consistent with the finding of Wålinder et al (2009) concerning the higher filling ratio of lumens at higher WPG levels. Additionally, as illustrated in Figure 1h,i, the furfurylated tracheids are completely or partly filled.…”
Section: D Microscopic Structuresupporting
confidence: 82%
“…For instance, acetylation was observed by electron microscopy (EM), and no evidence was found for cell wall damages or significant change in the microstructure (Sander et al 2003). In another scanning electron microscopy (SEM) study (Wålinder et al 2009), it was shown that some micro-structural changes may occur in situ polymerization during furfurylation, like polymer-filled lumen and microcracks in the cell walls. However, microstructural properties and remaining air-filled voids in acetylated and furfurylated wood samples are not yet quantified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, UV-laser ablation has been successfully used as a sample preparation technique for modified wood and wood-plastic composites (see e.g. Wålinder et al 2009;Laine et al 2014). …”
Section: Micromorphology Analysismentioning
confidence: 99%
“…2. For more information regarding the UV excimer laser see literature [17]. Samples exposed to natural weathering were not analysed using SEM due to continued exposure, hence the samples needed to stay intact.…”
Section: Sem Imagingmentioning
confidence: 99%